Fenretinide Inhibits Neutrophil Recruitment and IL-1β Production in Aspergillus fumigatus Keratitis. Issue 12 (December 2018) - Zhao, Wenyi; Che, Chengye; Liu, Kuixiang; Zhang, Jie; Jiang, Nan; Yuan, Kelan; Zhao, Guiqiu
Abstract : Purpose: Fungal keratitis is a major cause of corneal ulcers, resulting in significant visual impairment and blindness. Fenretinide, a derivative of vitamin A, has been shown to suppress inflammation in a multitude of diseases. In this study, we aimed to characterize the effect of fenretinide in Aspergillus fumigatus keratitis of the eye in a mouse model. Methods: In vivo and in vitro experiments were performed in mouse models and THP-1 macrophage cell cultures infected with A. fumigatus, respectively. Experimental subjects were first pretreated with fenretinide, and then the effect of the compound was assessed with clinical evaluation, neutrophil staining, myeloperoxidase assay, quantitative polymerase chain reaction (qRT-PCR), and western blot. Results: We confirmed that fenretinide contributed to protection of corneal transparency during early mouse A. fumigatus keratitis by reducing neutrophil recruitment, decreasing myeloperoxidase (MPO) levels and increasing apoptosis. Compared with controls, fenretinide impaired proinflammatory cytokine interleukin 1 beta (IL-1β) production in response to A. fumigatus exposure with contributions by lectin-type oxidized LDL receptor 1 (LOX-1) and c-Jun N-terminal kinase (JNK). Conclusions: Together, these findings demonstrate that fenretinide may suppress inflammation through reduced neutrophil recruitment and inflammatory cytokine production in A. fumigatus keratitis.